1198. Measurement of Pre-transplant Anti-cytomegalovirus (CMV) Immunoglobulin G Titer to Predict Risk of CMV Infection in CMV-seropositive Kidney Transplant Recipients. (31st December 2020) - Kirisri, Similan; Vongsakulyanon, Apirom; Kantachuvesiri, Surasak; Bruminhent, Jackrapong
Abstract: Background: Although cytomegalovirus (CMV)-seropositive solid organ transplant recipients have a lower risk of CMV infection compared with CMV-seronegative recipients, some patients remain at risk of CMV infection after transplant. Low pre-transplant anti-CMV immunoglobulin G (IgG) titer has been reported as a predictor of CMV infection in CMV-seropositive liver and heart transplant recipients, but this association in CMV-seropositive kidney transplant (KT) recipients has not been explored. We investigated the pre-transplant anti-CMV IgG titer and other CMV infection risk factors in CMV-seropositive KT recipients. Methods: This retrospective study was conducted on CMV-seropositive KT recipients aged > 18 years old at Ramathibodi Hospital during 2017 and 2018. The cumulative incidence of CMV infection was estimated with Kaplan–Meier methodology. The pre-transplant anti-CMV IgG titer was measured with an enzyme-linked fluorescent immunoassay. Risk factors for CMV infection were analyzed with Cox proportional hazards models. Results: Of the 340 included CMV-seropositive KT recipients (37% female; age [mean±SD]: 43±11 years), 69% and 64% received deceased-donor allograft and induction therapy, respectively. The anti-CMV IgG titer was < 20 and > 20 AU/ml in 7.1% and 92.9% of patients, respectively. During a mean follow-up of 14 months, the cumulative incidence of CMV infection was 14.8%, including both asymptomatic CMV infection (69%) and tissue-invasive disease (31%). A pre-transplant anti-CMV IgG titer of < 20 AU/ml was significantly associated with CMV infection in both the univariate analysis (HR, 2.70; 95%CI, 1.21–6.05, [ p =0.02]) and the multivariate analysis (HR, 2.98; 95% CI, 1.31–6.77, [ p =0.009]). Other significant risk factors of CMV infection included older donor age (HR, 1.03; 95% CI, 1.01–1.06, [ p =0.005]), anti-thymocyte induction therapy (HR, 2.90; 95% CI 1.09–7.74, [ p =0.033]), and prolonged cold ischemic time (HR, 1.06; 95% CI, 1.02–1.10, [ p =0.002]). Conclusion: A low pre-transplant CMV-specific humoral immunity is independently associated with post-transplant CMV infection in CMV-seropositive KT recipients. The universally available anti-CMV IgG titer test could potentially stratify those at risk and target preventive strategy appropriately. Disclosures: All Authors : No reported disclosures